The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12911-022-01945-z
|View full text |Cite
|
Sign up to set email alerts
|

Mobile health platform based on user-centered design to promote exercise for patients with peripheral artery disease

Abstract: Background Peripheral artery disease (PAD) is a cardiovascular disease that can be improved by risk factor modification. Mobile health (mHealth) intervention is an effective method of healthcare delivery to promote behavior changes. An mHealth platform can encourage consistent involvement of participants and healthcare providers for health promotion. This study aimed to develop an mHealth platform consisting of a smartphone application (app) synchronized with a wearable activity tracker and a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Additionally, patient-centered considerations of the design and interface before the development of an app might be helpful to promote behavior change. One study suggested iterative development through a user-centered design approach involving the following 3 phases: analysis, design, and implementation to achieve less fragmented care [54]. This systematic approach could encourage patients, survivors, and health care providers to participate in the development and quality assessment of mobile apps.…”
Section: Recommendations For Future Developmentmentioning
confidence: 99%
“…Additionally, patient-centered considerations of the design and interface before the development of an app might be helpful to promote behavior change. One study suggested iterative development through a user-centered design approach involving the following 3 phases: analysis, design, and implementation to achieve less fragmented care [54]. This systematic approach could encourage patients, survivors, and health care providers to participate in the development and quality assessment of mobile apps.…”
Section: Recommendations For Future Developmentmentioning
confidence: 99%
“…The text message library may be revised through this process; subsequently, the effectiveness of an EMA-triggered text message intervention should be investigated in patients with PAD. The developed text message library combined with the EMA survey may be applied to structure exercise programs or smartphone-based exercise intervention programs (Kim et al, 2022a) to encourage exercise engagement.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, barriers to exercise in patients with PAD were reported to include personal and environmental aspects (Abaraogu et al, 2018; Barbosa et al, 2015; Bentley & Kelechi, 2018; Cavalcante et al, 2015), but it is necessary to identify any additional barriers that might be present in the Korean population through behavior analysis. Therefore, we conducted face-to-face interviews to explore participants’ experiences performing exercise and focused on deriving exercise barriers and facilitators for the development of a text messaging intervention using a mobile application for patients with PAD (Kim et al, 2022a).…”
Section: Methodsmentioning
confidence: 99%
“…1) Personalized health monitoring: These systems use AI technologies to collect, process, and analyze health-related data, allowing for personalized health monitoring and support to the users. The automatic collection of data, such as vital signs, physical activity levels, and sleep patterns, can help detect health-related issues in real-time [8], [49], [61], [69].…”
Section: B Opportunitiesmentioning
confidence: 99%
“…One of the main advantages of these systems is their ability to provide users with real-time feedback, allowing www.ijacsa.thesai.org them to make informed health decisions [3]. Furthermore, these systems can offer personalized health recommendations, such as lifestyle changes or exercise programs [69] to assist users in improving their overall health.…”
Section: B Opportunitiesmentioning
confidence: 99%